Monitoring beam charge during FLASH irradiations - Vojnovic, Borivoj; Tullis, Iain D. C.; Newman, Robert G.; Petersson, Kristoffer (Frontiers in Physics, 2023)
In recent years, FLASH irradiation has attracted significant interest in radiation research. Studies have shown that irradiation at ultra-high dose rates (FLASH) reduces the severity of toxicities in normal tissues compared to irradiation at conventional dose rates (CONV), as currently used in clinical practice. Most pre-clinical work is currently carried out using charged particle beams and the beam charge monitor described here is relevant to such beams.Any biological effect comparisons between FLASH and CONV irradiations rely on measurement of tissue dose. While well-established approaches can be used to monitor, in real time, the dose delivered during CONV irradiations, monitoring FLASH doses is not so straightforward. Recently the use of non-intercepting beam current transformers (BCTs) has been proposed for FLASH work. Such BCTs have been used for decades in numerous accelerator installations to monitor temporal and intensity beam profiles. In order to serve as monitoring dosimeters, the BCT output current must be integrated, using electronic circuitry or using software integration following signal digitisation. While sensitive enough for FLASH irradiation, where few intense pulses deliver the requisite dose, the inherent insensitivity of BCTs and the need for a wide detection bandwidth makes them less suitable for use during CONV 'reference' irradiations.The purpose of this article is to remind the FLASH community of a different mode of BCT operation: direct monitoring of charge, rather than current, achieved by loading the BCT capacitively rather than resistively. The resulting resonant operation achieves very high sensitivities, enabling straightforward monitoring of output during both CONV and FLASH regimes. Historically, such inductive charge monitors have been used for single pulse work; however, a straightforward circuit modification allows selective resonance damping when repetitive pulsing is used, as during FLASH and CONV irradiations. Practical means of achieving this are presented, as are construction and signal processing details. Finally, results are presented showing the beneficial behaviour of the BCT versus an (Advanced Markus) ionisation chamber for measurements over a dose rate range, from <0.1 Gys -1 to >3 kGys -1